Association Between Acute Fall in Estimated Glomerular Filtration Rate After Treatment for Primary Aldosteronism and Long-Term Decline in Renal Function. Issue 3 (September 2019) - Kobayashi, Hiroki; Abe, Masanori; Nakamura, Yoshihiro; Takahashi, Katsutoshi; Fujita, Megumi; Takeda, Yoshiyu; Yoneda, Takashi; Kurihara, Isao; Itoh, Hiroshi; Tsuiki, Mika; Wada, Norio; Ichijo, Takamasa; et al.
Abstract : Primary aldosteronism causes renal structural damage after glomerular hyperfiltration, and primary aldosteronism-specific treatment leads to an acute fall in estimated glomerular filtration rate (eGFR). We investigated whether this change affected the long-term eGFR slope in a retrospective cohort from the multicenter Japan Primary Aldosteronism Study. We allocated patients with primary aldosteronism to the adrenalectomy (n=202) and MR (mineralocorticoid receptor) antagonist (n=303) groups based on their treatment history and analyzed the association between the initial eGFR fall and long-term eGFR slope. The increased age, low serum potassium levels, high eGFR, and high plasma aldosterone levels were independent predictors for a large initial eGFR fall in both groups. Our analysis of tertiles based on the initial eGFR fall revealed that in the MR antagonist group, patients with a small initial eGFR fall had a significantly steeper long-term eGFR slope than those with a large initial fall (tertile 1 versus 2, P =0.025; tertile 1 versus 3, P =0.017). These associations were not identified in the adrenalectomy group. Thus, the smaller the acute fall in eGFR by initiation of MR antagonists, the greater was the rate of long-term eGFR decline. While the acute fall in eGFR induced by primary aldosteronism-specific treatment is occasionally a clinical concern, our findings highlight the favorable implications of the acute fall with respect to long-term renal outcomes. Abstract : Supplemental Digital Content is available in the text.